Performance and operational effectiveness of evacuated flat plate solar collectors compared with conventional thermal, PVT and PV panels. (15th April 2018) - Moss, R.W.; Henshall, P.; Arya, F.; Shire, G.S.F.; Hyde, T.; Eames, P.C.
Highlights: A high vacuum increases efficiency and reduces heat losses. Test results were in good agreement with theoretical models. 50% higher efficiency than conventional panels or tubes at T M = 100 ° C, G = 1000 W/m 2 . 104% increase over conventional flat plate in predicted heat to district main operating at 85 °C. PVT panels are more effective than organic Rankine cycles for low temperature heat and power. Abstract: The concept of an evacuated flat plate (EFP) collector was proposed over 40 years ago but, despite its professed advantages, very few manufacturers have developed commercial versions. This situation suggests both technical difficulties in manufacturing a competitively-priced sealed for life panel and a lack of awareness of the benefits of such panels. This paper demonstrates an evacuated flat plate simulation that closely models experimental efficiency measurements. Having established the validity of the model, it compares published data for a commercial EFP collector with predictions for an optimal design to investigate whether any further efficiency improvement might be possible. The optimised design is then evaluated against alternative solar energy devices by modelling a number of possible applications. These comparisons should inform choices about solar options for delivering heat: EFP collectors are well-suited to some of these applications. Evacuated flat plate collectors are a possible alternative to concentrating collectors for Organic Rankine Cycle power generation. The annual output for all the modelled collectors was found to be a quadratic function of delivery temperature: this enabled a novel optimisation of ORC source temperature. Predictions for concentrating and non-concentrating ORC plant are compared with a PV/thermal alternative. The ORC output is significantly less than a PV panel would achieve; applications needing both heat and power are better served by PVT panels. This is an original and novel result.